Aging Anxiety Association with Body Objectification - Viskontaitė, Agota; Gegieckaitė, Goda; Gulbinaitė, Kotryna; Lapinskaitė-Vvohlfahrt, Elena; Petraškaitė, Karolina (Psichologija, 2025)
While aging is a natural and inevitable phenomenon, aging anxiety remains an under-researched aspect of the aging experience. The individual’s tendency to objectify one’s body might be related to more anxiety about the aging process. In this study, we aimed to explore how aging anxiety is related to body objectification. A total sample of 525 participants, ranging in age from 18 to 82, was included in the study. Correlational and regression analyses revealed a link between aging anxiety and body objectification. Body objectification dimensions, as well as worse subjective health, were significant predictors of the overall aging anxiety and most of its dimensions. Gender and not having children were also significant predictors for some of the aging anxiety dimensions.